The role of RNA m6A methylation in lipid metabolism - Wang, Yuting; Wang, Yujie; Gu, Jiarui; Su, Tianhong; Gu, Xiaosong; Feng, Yu (Frontiers in Endocrinology, 2022)
Abstract: The m6A methylation is the most numerous modifications of mRNA in mammals, coordinated by RNA m6A methyltransferases, RNA m6A demethylases, and RNA m6A binding proteins. They change the RNA m6A methylation level through their specific manner. The RNA m6A modification has significant impacts on lipid metabolic regulation. The “eraser” FTO and the “writer” METTL3/METTL14 can promote the accumulation of lipids in various cells, affecting the decomposition and synthesis of lipids. And the ‘reader’ YTHDF recognizes m6A methylation sites of RNA and regulates the target genes’ translation. Due to this function that regulates lipid metabolism, RNA m6A methylation plays a pivotal role in metabolic diseases and makes it a great potential target of therapy.